The Role of Batik in Indonesia’s National Identity and Global Fashion Trends - Akbar, Sutan; El Muna, Zuhairoh; Karim, Ruhana Abdul (Indonesia Discourse, 2024)
Batik, a traditional Indonesian textile art, holds a deep cultural significance that has long been associated with national identity. However, while much has been written about Batik’s historical and cultural relevance, there remains a lack of comprehensive analysis on how it has evolved within contemporary global fashion trends and its role in shaping Indonesia's modern national identity. This paper aims to fill this gap by exploring Batik’s dual significance: as a symbol of cultural heritage and as an increasingly influential element in the global fashion industry. Despite Batik’s recognition by UNESCO as an Intangible Cultural Heritage, its adaptation to modern fashion contexts and the economic implications of this transition are often overlooked. By addressing these issues, the study provides insights into how Batik has transcended its traditional role and is now contributing to global fashion while reinforcing its cultural and national importance.